Contributions to the cranial morphology of Pseudotriton ruber ruber (Sonnini) - Joubert, P. J.(Petrus Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1960.